2017
DOI: 10.3324/haematol.2017.182675
|View full text |Cite
|
Sign up to set email alerts
|

The role of SIRT6 in tumors

Abstract: Dysfunctional DNA-damage response and consequent genomic instability play a pivotal role in the initiation and progression of both solid and hematologic tumors. Preservation of DNA integrity is, in fact, a key cellular function, hence several mechanisms that repair the damaged DNA need to be studied. Recent studies have focused on key players that are able to improve the DNA repair and thus may act as targets for new therapeutic approaches.Several data have been obtained on overexpression and hyperactivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Acting as a tumour suppressor gene, FOXN3 is reduced in several types of tumours, such as HCC, colon cancer and osteosarcoma, but it is upregulated in ovarian cancer and breast cancer, where it acts as an oncogene . One explanation for the diverse effects of FOXN3 may be due to the specific cellular and tissue environment . In our previous studies, the forced expression of FOXN3 inhibited cell proliferation, the induction of apoptosis, and cell cycle arrest .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Acting as a tumour suppressor gene, FOXN3 is reduced in several types of tumours, such as HCC, colon cancer and osteosarcoma, but it is upregulated in ovarian cancer and breast cancer, where it acts as an oncogene . One explanation for the diverse effects of FOXN3 may be due to the specific cellular and tissue environment . In our previous studies, the forced expression of FOXN3 inhibited cell proliferation, the induction of apoptosis, and cell cycle arrest .…”
Section: Discussionmentioning
confidence: 82%
“…11,29 One explanation for the diverse effects of FOXN3 may be due to the specific cellular and tissue environment. 30,31 In our previous studies, the forced expression of FOXN3 inhibited cell proliferation, the induction of apoptosis, and cell cycle arrest. 21 These results indicated that FOXN3 may participate in the malignant transformation of leukaemia cells.…”
Section: Discussionmentioning
confidence: 89%
“…In these tumors, expression levels of SIRT6 are decreased and aerobic glycolysis pathways are blocked. In other cancer types, such as lung cancer (Desantis et al, 2018), prostate cancer (Bai et al, 2016), melanoma, and non-melanoma skin cancer (Garcia-Peterson et al, 2017), SIRT6 is upregulated both at mRNA and protein level, and acts as an oncogene responsible for cancer cell proliferation.…”
Section: Sirtuins and Cancermentioning
confidence: 99%
“…Inhibition of cytoplasmic SIRT1 promotes caspase-2-dependent apoptosis in breast cancer cells by promoting dissociation of its negative regulator, 14-3-3ζ (Andersen et al, 2011). SIRT6 functions as a master regulator of metabolic programming and maintains genome integrity during tumorigenesis (Desantis, Lamanuzzi, & Vacca, 2018). SIRT6 has high tumorigenic activity, and high expression of SIRT6 in colon cancer samples has been shown to correlate with poor prognosis (Geng et al, 2018).…”
Section: Nuclear Nad + Poolmentioning
confidence: 99%